Effects of efpeglenatide versus liraglutide on gastric emptying, glucose metabolism and beta-cell function in people with type 2 diabetes: an exploratory, randomized phase Ib study. Issue 1 (25th June 2021) - Hompesch, Marcus; Kang, Jahoon; Han, OakPil; Trautmann, Michael E; Sorli, Christopher H; Ogbaa, Ike; Stewart, John; Morrow, Linda
Abstract : Introduction: To evaluate the effects of efpeglenatide, a long-acting glucagon-like peptide-1 receptor agonist (GLP-1 RA), on gastric emptying, glucose metabolism, and islet beta-cell function versus liraglutide and placebo in people with type 2 diabetes. Research design and methods: This phase Ib study (ClinicalTrials.gov identifier: NCT02059564 ) randomized participants (n=47) to three cohorts. Within the first two cohorts, participants were randomized to placebo, efpeglenatide 6 mg weekly (QW; first cohort), or efpeglenatide 16 mg monthly (QM; second cohort). The third cohort received liraglutide 1.8 mg daily (QD). Gastric emptying was assessed through the pharmacokinetic (PK) profile of acetaminophen at baseline and steady state. Glucose metabolism and beta-cell function were assessed based on mixed-meal tolerance testing and a graded glucose infusion procedure. Results: Treatment duration was approximately 3 months for efpeglenatide 16 mg QM and 1 month for efpeglenatide 6 mg QW and liraglutide. At peak drug concentrations, efpeglenatide 6 mg QW was non-inferior to liraglutide 1.8 mg QD in delaying gastric emptying, as assessed by acetaminophen PK (lower bound of 90% CI for the efpeglenatide:liraglutide ratio >0.8 for area under the curve (AUC)0–120, AUC0–180, AUC0–360 and maximum concentration (Cmax )). Efpeglenatide 16 mg QM did not decrease the rate of gastric emptying to as great an extent as liraglutide (ie, non-inferiority was not shown). Compared with liraglutide, both efpeglenatide dosing regimens demonstrated comparable or more favorable glucometabolic effects and improved beta-cell function. All gastrointestinal adverse events reported with efpeglenatide were mild or moderate in severity and transient over treatment and follow-up. Conclusions: The glucometabolic effects of efpeglenatide 6 mg QW and 16 mg QM were comparable to liraglutide. Additional studies are necessary to further examine these benefits of efpeglenatide. Trial registration number: NCT02059564 .